Different cover crops have a limited impact on marketable yields and biogeochemical cycling but secondary effects on pollinators and plant-parasitic nematodes in Florida organic vegetable systems - Allar, John; Mallinger, Rachel; Liu, Chang; Grabau, Zane; Maltais-Landry, Gabriel (Frontiers in Sustainable Food Systems, 2023)
Cover crops are typically grown during the summer in Florida's organic vegetable systems, where they can affect nutrient cycling, soil health, and pests/pollinators. We compared the effects of five summer cover crops and a weedy fallow on marketable yields and the cycling of phosphorus, potassium, and carbon. Weed, nematode, and insect pollinator abundance were also monitored to measure any secondary impacts of cover cropping. Cover crops included monocultures of sunn hemp or sorghum sudangrass, a sunn hemp and sorghum sudangrass biculture, a three species mixture (biculture plus buckwheat), and a five species mixture (three species mixture plus cowpea and sunflower). In both 2018 and 2019, cover crops were planted in June and terminated in August, and bell peppers were grown from August until December. Marketable yields were greater with the tree and five species mixtures relative to the biculture in 2018, with no effects of cover crops on yields in 2019. Phosphorus and potassium accumulation was typically greater with cover crops than in the weedy fallow, but cover crops did not affect pepper nutrient accumulation or soil concentrations. Similarly, differences in carbon accumulation (lowest in sorghum sudangrass monoculture and weedy fallow) did not affect soil organic matter, soil total carbon or permanganate-oxidizable carbon. When analyzed as part of a radar plot analysis, cover crops helped manage summer weeds and rootknot nematodes in 2019, but the sorghum sudangrass monoculture increased sting nematodes; only the three and five species mixtures benefitted pollinators as buckwheat was the only cover crop that flowered in this study. Overall, cover crops had a limited effect on marketable yields and biogeochemical cycling but had more important secondary effects on pests and pollinators.